Broadband and extremely low frequency sound isolation by a programmable shunted electromechanical diaphragm with force dipole effect. (15th June 2021) - Wu, Keming; Huang, Lixi; Zhang, Xingyu; Liu, Xiang; Wang, Chunqi; Zhang, Yumin
Highlights: Force dipole effect is proposed and realized by passive feedback mechanism in experiment, contrasting to the feed-forward principle of membrane-type acoustic metamaterials The device, SEMD, with the force dipole effect breaks mass law and stiffness laws in 5.7 octaves and down to infrasound range SEMD and its force dipole effect is electronically programmable Verified lumped parameter model predicts that a superconducting circuit creates super broadband band gap for sound transmission, such as over 60 dB sound attenuation in 10Hz - 2000 Hz. Abstract: Broadband sound isolation in low frequencies by a partition with a small dynamic mass is a challenge to the mass law. We review the conventional sound isolation panels and membrane-type acoustic metamaterials and find that the former is equivalent to a monopole identical to a single path control system and the latter is similar to a dipole equivalent to a feed-forward system with zero time delay. Neither is likely to enhance sound isolation in a broad bandwidth and at low frequencies. Here, we introduce a "force dipole" effect, which is a passive feedback force countering the incident sound. The device is based on a passively shunted electromechanical diaphragm (SEMD), consisting of a moving-coil attached diaphragm, a permanent magnet generating a DC magnetic field, and a programmable analog circuit shunting the coil. It isolates sound in a super broad bandwidth down to the infrasound region. In reaction to an incident sound, a Lorentz force is exerted on the moving-coil opposing the incident pressure force, forming a near-perfect dipole. The net residual force is greatly reduced and so is the sound wave transmission. The force dipole effect is determined by the shunt circuit and our experiments in an impedance tube show that the spectrum of transmission loss (TL) of the SEMD can be programed by a smart circuit; it is maintained at 20 dB or above from 15 Hz to 772 Hz. The mass and stiffness laws are broken over 5.7 octaves. The lumped-parameter theoretical model is verified by experiment, and further analysis predicts that a superconducting circuit will achieve a super broadband band gap. Graphical abstract: Image, graphical abstract